Are physicians changing the way they practise obstetrics? - Ruderman, J (1993)
OBJECTIVE: To examine trends in obstetric interventions in women at low risk over approximately 3 years. It was postulated that there would be a general reduction in most intervention rates. DESIGN: Retrospective review of hospital records. SETTING: Three downtown hospitals of the University of Toronto, in which academic and nonacademic family physicians and obstetricians practised. PATIENTS: A total of 2365 women in phase 1 (April 1985 to March 1986) and 1277 in phase 2 (May to September 1988) met the inclusion criteria for grade A (pregnancy at no predictable risk) of the Ontario Antenatal Record at the time of admission to hospital. OUTCOME MEASURES: Rates of artificial rupture of the membranes, induction, augmentation, epidural anesthesia, continuous electronic fetal monitoring (EFM), instrumental delivery, episiotomy and cesarean section. RESULTS: The family physicians and the obstetricians had significant decreases (p < 0.01) over time in the rates of episiotomy, especially mediolateral, and low forceps delivery. The rate of epidural anesthesia decreased significantly in the obstetrician group. The rates of artificial rupture of the membranes, induction and continuous EFM increased in the two physician groups; the increased rate of EFM was significant in the obstetrician group (p < 0.01). There was no significant change in the rates of augmentation, midforceps delivery, vacuum extraction or cesarean section. All of the trends were found to hold when the intervention rates were analysed according to the women's parity. CONCLUSIONS: Some of the findings reflect recommendations and trends reported in the literature, whereas others are not supported by clear medical evidence. The unpredictable nature of the trends suggests that further study is warranted of the reasons for obstetric trends and for the changes in physicians' practice patterns.